MODEL MANAJEMEN KONFLIK PERNIKAHAN BEDA AGAMA DALAM PEMIKIRAN AHMAD NURCHOLISH - Amalia, Tyas (Jurnal Sosiologi Agama, 2018)
Interfaith marriage is still an interesting theme to be discussed which is full of controversy. Ahmad Nurcholish and Ang Mei Yong were one of the phenomenal interfaith marriages in Indonesia in 2003. This study focused on the conflict management model of interfaith marriage undertaken by both. Ahmad Nurcholish is a devout Muslim, and Ang Mei Yong is a Confucian. The interfaith marriages that are lived by them are mutual agreements without any element of coercion. According to Ahmad Nurcholish, to deal with interfaith marriages there are at least 3 models, namely: self-reflection, asking for advice from the closest person, and presenting mediators, through the process of externalization, objectification, and internalization. While in conflict management there are several aspects, namely, competency, collaboration, compromise, avoidance, and accommodating. Keywords: Marriage different religion, Ahmad Nurcholis, Social Construction, Conflict Management Abstrak Pernikahan beda agama masih menjadi tema menarik untuk diperbincangkan yang sarat akan kontroversi. Ahmad Nurcholish dan Ang Mei Yong merupakan salah satu pelaku nikah beda agama di Indonesia yang fenomenal pada tahun 2003. Kajian ini, memfokuskan pada model manajemen konflik Nikah beda agama yang dijalani oleh keduanya. Ahmad Nurcholish yang beragama Islam taat, dan Ang Mei Yong yang beragama Khonghucu. Pernikahan beda agama yang dijalani keduanya merupakan kesepakatan bersama tanpa ada unsur paksaan. Menurut Ahmad Nurcholish, untuk menangani nikah beda agama setidaknya ada 3 model, yaitu: refleksi diri, minta saran orang terdekat, dan menghadirkan mediator, melalui proses eksternalisasi, objektivikasi, dan internalisasi. Sementara dalam memanajemen konflik ada beberapa aspek yaitu, kompetesi, kolaborasi, kompromi, menghindar, dan mengakomodasi. Kata Kunci: Nikah Beda Agama, Ahmad Nurcholis, Konstruksi Sosial, Manjemen Konflik